Dietary starch and fiber: potential benefits to body weight and glucose metabolism. (September 2011) - Chambers, Edward; Guess, Nicola; Viardot, Alexander; Frost, Gary
SUMMARY Dietary starch and fiber, particularly the fermentable content, may be important for long-term weight loss and the prevention and management of Type 2 diabetes. Resistant starch and most dietary fibers are fermented in the colon producing short chain fatty acids. Free fatty acid receptors 2 and 3 are two recently discovered receptors. The main ligands for these receptors are short chain fatty acids. These receptors are found on enteroendocrine L-cells in the colon where they stimulate the release of anorectic hormones (glucagon-like peptide-1 and peptide tyrosine tyrosine) and on adipocytes where they can exert improvements to insulin sensitivity. Recent studies have shown that supplementing the diet with fermentable fiber can have a positive effect on weight loss and insulin sensitivity. Further investigations with high-risk populations are warranted to determine if long-term dietary interventions with fermentable fibers can protect against or delay the progression of Type 2 diabetes.